Teaching Family Medicine - what, why and where - J.J. Blitz-Lindeque (South African Family Practice)
Inaugural address as Professor in Family Medicine, University of Pretoria, 28th May 2002. Julia Blitz-Lindeque graduated with MBBCh from Wits. She completed the Academy of Family Practice Vocational Training Scheme at the Edendale Hospital, Pietermaritzburg and Benedictine Hosptical, Nongoma and her MPraxMed at MEDUNSA. She then became a part-time facilitator of the Kwazulu M Fam Med group of MEDUNSA while in private general practice in Pietermaritzburg. In 1997, she joined the Department of Family Medicine at the University of Pretoria and was appointed Chief Family Physician, Pretoria Academic Hospital and the Professor and Head of Department of Family Medicine in June 2001. She is currently the Chairperson of the Family Medicine Education Consortium, the Vice-Chairperson of the Committee for General Practice of the Medical and Dental Professionals Board of the Health Professions Council, a Councillor of the College of the Family Practitioners and was the Associate Editor of the South African Family Practice Journal. She is interested in the appropriate teaching of the Family Medicine in South Africa at both an under-graduate and post-graduate level, research in the Family Medicine and the further development of our discipline.